Exploring Awareness Needs and Information Display Preferences Between Coworkers - Brush, A.J.; Meyers, Brian; Scott, James; Venolia, Gina (CHI '09 Proceedings of the SIGCHI Conference on Human Factors in Computing Systems, 2009)
Technology makes it possible to share many different types of information with coworkers. We conducted a large-scale survey (N=549) to better understand current sharing among coworkers, how people stay aware of collocated and remote coworkers, and whether their willingness to share different types of awareness information changes based on the location in which the information is displayed. Contrary to our expectations, the display location did not greatly affect what respondents were willing to share. Our results also suggest considerations for researchers building situated displays, as respondents had concerns about unintended viewers and encouraging people to visit their personal space when they were not present.